2019
DOI: 10.1186/s12978-019-0796-4
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of maternal and newborn health outcomes through a clinical mentorship program in the Democratic Republic of the Congo: study protocol

Abstract: Background The Democratic Republic of the Congo (DRC) boasts one of the highest rates of institutional deliveries in sub-Saharan Africa (80%), with eight out of every ten births also assisted by a skilled provider. However, the maternal and neonatal mortality are still among the highest in the world, which demonstrates the poor in-facility quality of maternal and newborn care. The objective of this ongoing project is to design, implement, and evaluate a clinical mentorship program in 72 health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Progress in antenatal care has been made worldwide, which is also supported by our results [41]. Some studies indicate that not only should recommendations be implemented but also "active clinical mentoring" (including such activities as organizing and training a national team of mentors including senior midwives, obstetricians and pediatricians) should be used to improve health awareness even before pregnancy [42]. The meta-analysis by Miteniece E et al indicated other issues that should be improved, with the geographical distance to healthcare institutions being one of the most important [43].…”
Section: Discussionsupporting
confidence: 76%
“…Progress in antenatal care has been made worldwide, which is also supported by our results [41]. Some studies indicate that not only should recommendations be implemented but also "active clinical mentoring" (including such activities as organizing and training a national team of mentors including senior midwives, obstetricians and pediatricians) should be used to improve health awareness even before pregnancy [42]. The meta-analysis by Miteniece E et al indicated other issues that should be improved, with the geographical distance to healthcare institutions being one of the most important [43].…”
Section: Discussionsupporting
confidence: 76%
“…In Tanzania, these topics are prioritized in local RMNH manuals and guidelines, for instance, the Essential Newborn Care Guideline, the Basic Emergency Obstetric & Newborn Care Training manual, and the Comprehensive Emergency Obstetric and Newborn Care training manuals, just to cite a few (22)(23)(24). These topics have also been prioritized in CM intervention (6)(7)(8)(9)(10)(11)25) and suggested by the WHO as key capacity-building areas for improving maternal and newborn service delivery in healthcare facilities (26). Moreover, recent studies in the country have identified some of these topics as priority areas that need capacity building.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer Ethiopian mentees (39%) reported their clinical skills improved to a great extent compared to Tanzanian mentees (74%). The combined effect of training and mentorship may be more effective [ 62 ] and future surgical mentorship programs should consider clinical training before mentorship and clinical mentorship during visits [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%